THE ROLE OF INVERSION IN LITERARY TEXTS AND MODERN LIFE - Saloxiddinova Sevara Abdiraxmonovna; Nurmatova Raʼno Abror qizi (TADQIQOTLAR, 2026)
Abstract. This study investigates the process of syntactic inversion and analyzes its impact on literary discourse. The primary objective of this article is to demonstrate the  transformation  of  the  standard  English  Subject-Verb-Object  (SVO)  pattern  by interpreting the positioning of the noun phrase before the verb as subject-marking. Through  an  examination  of  various  literary  excerpts,  this  research  categorizes  the diverse functions of inversion. Specifically, the analysis explores examples from John Milton’s poetry as well as common negative sentences used in dail life. The research shows that flipping the standard SVO order does more than just make a sentence sound formal; it creates a specific rhythm and highlights the most important information. Ultimately, the article demonstrates how inversion helps authors add emotion and make their writing more powerful.